Avaliação da resistência à corrosão de aços AISI 430 recobertos por filmes finos de ZrSiN - Charliane Pereira Ferreira (2016)
Flexible ducts are used in the so-called pre-salt oil extraction and the innermost structure of these ducts, called casing, is the only metal part in direct contact with the produced oil, and, therefore, it is subject to the fluid components corrosive action, especially to the corrosive action of saline solutions. One of the feasible alternatives to reduce corrosion effects in these flexible lines is the use of transition metal nitrides thin films, individually or deposited in layers of two or more materials alternately one over the other. This study aims to analyze the corrosion behavior of ZrN thin films, and these coatings with Si addition in different percentage, all of them deposited on AISI 430 steel by the magnetron sputtering technique. Corrosion resistance was evaluated using the electrochemical impedance spectroscopy (EIS) technique, in 3.5% (w/v) NaCl solution. The samples surface characterization was carried out by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) analysis. The results showed that the sample preparation and the deposition parameters are essential to the coatings structure and properties. It was also observed that Si addition enhance the ZrN-steel system corrosion performance, insaline medium.